10.1016/s0029-7437(08)70194-0 (CrossRef Listing of Deleted DOIs, 2000)
Objectives To describe the first reported case of embolic stroke with hemorrhagic conversion following a dermatologic energy-based device procedure, highlighting its mechanism and clinical implications. Methods A detailed case review was conducted, including clinical presentation, imaging, and subsequent diagnostic workup. The patient provided consent for publication. Results A 62-year-old woman with a history of Chiari malformation, hypertension, and hyperlipidemia underwent full-field ablative Erbium:YAG laser resurfacing for facial photodamage. During the procedure, she experienced significant pain and performed a Valsalva maneuver. Post-procedure, she developed persistent blurry vision and occipital pain. Seven days later, she presented to the emergency department with left homonymous hemianopsia. Neuroimaging demonstrated a right posterior cerebral artery embolic infarct with hemorrhagic conversion. Cardiac evaluation identified a patent foramen ovale (PFO) with right-to-left shunt provoked by Valsalva, consistent with paradoxical embolism. She was managed conservatively with aspirin and high-intensity statin therapy. Six months later, she underwent percutaneous PFO closure. At follow-up, her hemianopsia persisted, while occipital pain and swelling had fully resolved. Conclusions Post-procedural stroke is a rare, life-threatening complication that may occur after medical interventions, including energy-based dermatologic procedures. In this case, paradoxical embolism through an undiagnosed PFO, facilitated by intraprocedural Valsalva, was the likely mechanism. Dermatologists should remain vigilant for this possibility and optimize pain control to reduce Valsalva and associated thromboembolic risk.